Video-assisted thoracic surgery (VATS) right lower lobectomy after neoadjuvant treatment – case report - Vela Ilir; Nexhati Jakupi; Dzikovksi Igor (My University, 2022)
Lung cancer is the most common cause of cancer-related death in men and second-most common in women. While surgical resection offers the best chance of curing those with early-stage lung cancer, the traditional open-chest approach (called a thoracotomy) typically requires five to seven days of recovery in the hospital, with an extended recovery at home. Over the past two decades, video-assisted thoracic surgery (VATS) has revolutionized how thoracic surgeons diagnose and treat lung diseases. This video-assisted thoracic surgery (VATS) technique reduces a patient's hospital stay to about three to four days, and the patient experiences a more rapid recovery with less pain after VATS lobectomy surgery as compared with the traditional thoracotomy approach. We report a VATS right lower lobectomy case in a 65-year-old patient with post neoadjuvant therapy for adenocarcinoma. With pre-surgical tests, which include: a complete physical exam, CT scan, PET scan, bronchoscopy, blood test, electrocardiogram and spirometry. The patient was proposed for two-portal thoracoscopic surgery. The patient was placed in a left lateral decubitus position, and a double incision was performed at the anterior level of the 5th intercostal space (4 cm incision) and the second one at the level of the 8th intercostal space (2 cm incision). A right lower lobectomy with a two-portal technique was successfully performed. The postoperative course was without complications, and the patient was discharged home on the 4th postoperative day. The two-portal video-assisted thoracoscopic surgery (VATS) approach is an excellent option for lung cancer management, offering a quick recovery and low morbidity.
Keywords: video-assisted thoracic surgery (VATS); right lower lobectomy; lung cancer